(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Ophthalmology has a long history which is represented on numismatic materials. The branch of historical science numismatics (from the Latin "numisma" – coin) originated in the 19th century and became closely related to economics, politics, culture and law, and includes the thematic study of coins, medals and plaques. The history of ophthalmology is best illustrated by various forms of medal art (exonum or paranumism), and the medal became the prototype of a commemorative (memorial) coin. In this work, the authors presented a catalog of 127 numismatic materials (105 medals, 6 plaques, and 16 coins), including some unique ones, presented for the first time. Numismatic materials depicting common international symbols of this science ("eye", including "eye on the palm", "owl", "pince-nez", "candle") were reflected and the stages of development of native ophthalmology presented. The paper includes also references to significant historical events in ophthalmology and a highlight of biographies of 16 scientists who contributed invaluably to the formation of this science and whose lives were associated with Ukraine. The medals show the portraits of the ancient Kyiv doctor Agapetus and the founders of modern world ophthalmology. Unfortunately, up to date, eminent oculists of the past have been not sufficiently commemorated by issues of numismatic pieces. Hence, it is our hope that in the future, a systematic approach to this matter as well as the purposeful promotion of the achievements of national ophthalmology by numismatics will be used, to provide a clear example for studying the history of ophthalmology and enhance the educational attainment of doctors.